Analisis Risiko dengan Metode ISO 31000 pada Disperinnaker Kota Salatiga Bidang Industri - Lela Dina Berliana; Andeka Rocky Tanamaah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Every government agency, must have administrative assets and application systems used, as well as the industrial sector of the Salatiga City Disperinnaker. From each of these activities, there must be threats and risks. To minimize it, a risk analysis is needed in order to prevent, treat, and improve the risks that occur. This risk analysis uses the ISO 31000 method. The ISO 31000 method is more perspective and conceptual compared to other ISO methods. There are 2 stages in this risk analysis, namely risk assessment and risk treatment. The purpose of conducting a risk analysis using the ISO 31000 method is to identify possible risks that arise and to know the level of impact of these risks and to come up with proposals for actions or efforts to minimize the risks that occur, both for assets and applications used in the Salatiga City Disperinnaker industry. so that activities can run optimally.